2020
DOI: 10.2147/cmar.s246609
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multi-Window CT Based Radiological Traits for Improving Early Detection in Lung Cancer Screening</p>

Abstract: Rationale and Objectives: Evaluate ability of radiological semantic traits assessed on multi-window computed tomography (CT) to predict lung cancer risk. Materials and Methods: A total of 199 participants were investigated, including 60 incident lung cancers and 139 benign positive controls. Twenty lung window features and 2 mediastinal window features were extracted and scored on a point scale in three screening rounds. Multivariate logistic regression analysis was used to explore the association of these rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our results are consistent with those of Yang et al, who showed that radiomics signatures from both plain and vein-phase CT images were not superior to either plain signatures or vein signatures in differentiating solitary granulomas and solid lung adenocarcinomas [ 14 ]. However, two recent studies on lung cancer indicated that multiple-window-based models performed better than single-window-based models [ 20 , 21 ]. For example, Lu et al found that when predicting lung tumour growth patterns from radiomics features, the models constructed based on the lung window or the difference region (subtracting the mediastinal window region from the lung window region) were inferior to the model established based on both of them [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of Yang et al, who showed that radiomics signatures from both plain and vein-phase CT images were not superior to either plain signatures or vein signatures in differentiating solitary granulomas and solid lung adenocarcinomas [ 14 ]. However, two recent studies on lung cancer indicated that multiple-window-based models performed better than single-window-based models [ 20 , 21 ]. For example, Lu et al found that when predicting lung tumour growth patterns from radiomics features, the models constructed based on the lung window or the difference region (subtracting the mediastinal window region from the lung window region) were inferior to the model established based on both of them [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most existing thresholding-based lung nodule detection techniques handle CT scan images consisting of lung windows only and do not consider the mediastinal windows in the detection of the disease. Research such as [33] has shown that the detection rate is improved if both windows are analyzed for lung nodules. On the other hand, deep learning requires a huge amount of data to train a model perfectly; it is challenging to obtain such an extensive dataset in the medical field, where imaging and tagging by experts is a tedious and expensive task.…”
Section: Introductionmentioning
confidence: 99%